Benthic control upon the morphology of transported fine sediments in a low‐gradient stream. Issue 11 (28th June 2013) - Fox, James; Ford, William; Strom, Kyle; Villarini, Gabriele; Meehan, Michelle
Abstract The structure of fluvial sediments in streams has environmental implications to contaminant fate, nutrient budgeting and the carbon flux associated with fine particulate organic matter (FPOM). However, the influence of sediment structure is lacking in environmental predictive models. To this end, the present study links field‐based results of sediment aggregate structure to seasonal biological functions in the surface fine‐grained laminae (SFGL) of a low‐gradient stream. Fluvial sediment collection, microscopy and image analysis are used to show that aggregates collected over a 20 month time period support the concept that aggregate structure can vary seasonally in low‐gradient streams where temporarily stored sediment is prominent. Results show that the structure of the transported aggregates is more irregular in the summer with the structure being elongated about the long axes. In the winter, the aggregate structure is compacted and more spherical. Statistical analysis and results suggest that heterotrophic and autotrophic biological activity within the SFGL exhibits seasonal control upon the morphology of transported sediments. Implications of this research are highlighted through calculations of the reactive surface area of the transported suspended sediment load. The surface area of transported sediment is estimated to be 40% greater in the summer as compared to the winter time period, which implies that (i) the affinity of sediments to sorb contaminants is higher in summer months and (ii) the downstream reactivity of FPOM in large rivers, lakes and estuaries is not just a function of microbial drivers but also the seasonally dependent structure of transported FPOM derived from low‐order streams. Copyright © 2013 John Wiley & Sons, Ltd.